EFFECT OF PLANTING MEDIA ON THE GROWTH OF Shorea pinanga Scheff. SEEDLINGS - Prameswari, Diana; Tata, Hesti Lestari (Secretariat of Forestry Research and Development Agency, 2004)
Shoreapinanga Scheff. is a major tropical plant species which has an important economic value not only for timber, but also as illipe nut (called tengkawang in local name) production. This species is suggested for land rehabilitation and forest conservation. In rehabilitation action, S. pi11a11ga is usually planted on the poor and degraded area. Application of chemical fertilizer and compost is used to increase the survival and growth of the seedlings. Excessive chemical fertilizer input to soil, however, may cause negative effect on soil, plant and environment. Conversely, compost may improve soil porosity, soil aggregate, water absorption and soil fertility. The objective of the study was to examine effect of planting media on growth of S. pinanga seedlings. Complete randomized design has been arranged with 5 treatments, e.g. soil mixed with husk (at the proportion of 1:1), soil mixed with acacia compost (1:1), soil mixed with charcoal of rice husk (1:1) and soil mixed with humic acid (1:1). Another treatment was soil alone used as control. The result showed that growth of both stem height and diameter, and index of seedling quality were affected significantly by planting media. The mixture of soil and acacia compost (1 :1) was the best planting media for the growth of S. pinanga seedlings, which resulted in the growth of height (24.19 cm) and stem diameter (0.246 cm). Meanwhile, soil mixed with rice husk charcoal (1:1) gave the best result to the index of seedling quality (ISQ = 1.34) and total dry weight (TOW= 15.93 g).